FAKTOR EKSPLOITASI MERANTI DI SUMATRA BARAT, KALIMANTAN BARAT DAN KALIMANTAN SELATAN - Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
A study on recovery in Meranti logging operation was carried out in West Sumatra and West Kalimantan in 1984, and in South Kalimantan in 1985. The purpose of this study is to determine recovery figures for Meranti at these particular locations, which may be use full in the planning efforts of logging companies.The study comes to the following conclusions :Average logging recovery for Meranti in West Sumatra, West Kalimantan and South Kalimantan is 0.84.Recovery among provinces and among forest companies do not differ significantly,Recovery between diameter classes differs significantly. It is suggested that logging of small diameter trees be done with care, to avoid leaving relatively small timber in the forest.